Hadith #4649 - Sunan al-Nasa'i - Abdul Malik bin 'Ubaid عبد الملك بن عبيد; Hajjaj bin al-Minhal حجاج بن المنهال; Ibn Jurayj ابن جريج; Ibrahim bin al-Hasan bin al-Hythm إبراهيم بن الحسن بن الهيثم; Isma'il bin Umayya bin 'Amr إسماعيل بن أمية بن عمرو (Sunan al-Nasa'i)
“I was with the Messenger of Allah on a journey, and I was riding a camel. He said: ‘Why are you at the back of the people?, I said: ‘My camel is tired, He took hold of its tail and shouted at it, then I was at the front of the people, worrying that it would go ahead of the others. When we drew close to al-Madinah he said: ‘What happened to the camel? Sell it to me.’ I said, No, it is yours O Messenger of Allah.; He said, ‘No, sell it tome. I said, ‘No, it is yours, O Messenger of
Grade:

Hadith #5186 - Sunan al-Nasa'i - Abdul Malik bin 'Ubaid عبد الملك بن عبيد; Abu Hurairah; Ahmed bin Hafs bin 'Abdullah أحمد بن حفص بن عبد الله; Bashayr bin Nahayk بشير بن نهيك السدوسي; Hafs bin 'Abdullah bin Rashid حفص بن عبد الله بن راشد; Ibrahim bin Sa'd bin Ibrahim إبراهيم بن سعد بن إبراهيم; Qatada قتادة (Sunan al-Nasa'i)
“The Messenger of Allah forbade me from wearing Al-Qassi, garments dyed with safflower, and gold rings.”
Grade:

Hadith #5274 - Sunan al-Nasa'i - Abdul Malik bin 'Ubaid عبد الملك بن عبيد; Abu Hurairah; Ahmed bin Hafs bin 'Abdullah أحمد بن حفص بن عبد الله; Bashayr bin Nahayk بشير بن نهيك السدوسي; Hafs bin 'Abdullah bin Rashid حفص بن عبد الله بن راشد; Ibrahim bin Tahman إبراهيم بن طهمان; Qatada قتادة (Sunan al-Nasa'i)
The Messenger of Allah said: “Allah has permitted silk and gold to the females of my Ummah, and has forbidden them to the males.”
Grade: